2020
DOI: 10.31236/osf.io/b75z9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of flywheel training on strength-related variables in female populations. A systematic review

Abstract: Background: This study aimed to evaluate the effect of flywheel training on female populations, report practical recommendations for practitioners based on the current available evidence, underline the limitations of current literature, and establish future research directions.Methods: Studies were searched through the electronic databases (PubMed, SPORTDiscus, and Web of Science) following the preferred reporting items for systematic reviews and meta-analysis statement guidelines.Results: The methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although flywheel training has been investigated with a variety of populations relating to strength, power, and athletic performance (1,6,52,65)—less is known about its efficacy in reducing interlimb asymmetries (9,28). Flywheel training exercises ranging from (bilateral, unilateral, lateral) squats to multidirectional movements have been applied with the objective of reducing interlimb asymmetries (27,31,43).…”
Section: Resistance Training Methods For Reducing Asymmetriesmentioning
confidence: 99%
“…Although flywheel training has been investigated with a variety of populations relating to strength, power, and athletic performance (1,6,52,65)—less is known about its efficacy in reducing interlimb asymmetries (9,28). Flywheel training exercises ranging from (bilateral, unilateral, lateral) squats to multidirectional movements have been applied with the objective of reducing interlimb asymmetries (27,31,43).…”
Section: Resistance Training Methods For Reducing Asymmetriesmentioning
confidence: 99%
“…The studies reported in this review have mainly involved male participants; however, the volume of literature pertaining to flywheel training studies using female populations is scarce (18,42). Because of the differences between male and female subjects in terms of physical fitness and responses to resistance training programs exist (e.g., because of different hormonal levels), further analysis to differentiate responses to flywheel and traditional resistance programs between sexes is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The main limitations on this topic are (a) the scarce inclusion of female samples in previous studies (42) and (b) the lower use of upper-limb exercises in flywheel training programs. In this regard, further studies should be performed on these topics.…”
Section: Introductionmentioning
confidence: 99%
“…Flywheel (FW) inertial resistance training has gained attention in recent years due to all the positive acute [1,2] and short-term [3] neuromuscular performance effects, and long-term effects derived from FW training interventions on strength, power (P), performance-related variables [4][5][6][7][8][9][10][11], and clinical outcomes [12][13][14]. There are many different FW devices on the market, all of which follow the same principle-by accelerating and then consequently braking the mass moment of inertia (I) of the FW.…”
Section: Introductionmentioning
confidence: 99%